Shelter Strategies for the Urban Poor: Idiosyncratic and Successful, but Hardly Mysterious - Buckley, Robert M.; Kalarickal, Jerry (World Bank, Washington, D.C., 2013)
In 1986 the World Bank prepared a strategy for low-income housing in developing countries. This work grew out of the Bank's efforts to support the urban poor through an extensive housing assistance program that was launched by Bank President McNamara's speech on urban poverty. By that time, the Bank had provided more than $4 billion of such assistance, and had undertaken an extensive research effort to design support for that lending. Much has changed since that time, not only in the way the Bank provides shelter assistance, more than doubling its support since that review, but also in the changing consensus as to what shelter strategy should be. The authors review the emerging consensus. They examine three new research areas: the empirical analysis of the effects policy has on housing supply; the richer understanding of the effects that land market regulations have on specific projects and on the functioning of urban areas; and the alleged mysterious effects that de Soto, for example, claims that effective property rights have not only for shelter policy but for development more generally. The authors also examine the emergence of both a new financial innovation, micro-enterprise finance, and the increased emphasis given to project design based on community participation, showing how these approaches more fully reconcile the incentives faced by beneficiaries and donors. In sum, the authors argue that the evolving consensus on shelter strategy is not nearly as mysterious as some would claim. Housing markets in most developing countries remain highly idiosyncratic and constrained. Nevertheless, the evolving consensus on shelter strategy appears to recognize these idiosyncrasies and policy constraints as evidenced by the strong and improving performance of the Bank's shelter lending.